Adaptasi Mahasiswa terhadap Teknologi Artificial Intelligence dalam Komunikasi Pendidikan: Studi Kasus Perguruan Tinggi di Lampung - Esyarito, Mohammad ‘Afief; Aryanti, Nina Yudha; Utaridah, Nanda; Kartika, Tina; Putra, Purwanto (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to explore how students adapt their communication in utilizing Artificial Intelligence (AI) in the educational context, and to examine its impact on interpersonal communication, academic integrity, digital literacy, and readiness for the workforce. A qualitative descriptive approach was employed, using data collected through a Google Form questionnaire completed by 105 student respondents. The data were analyzed thematically to identify patterns in student experiences. The findings reveal that 96,2% of students felt AI helped them understand course material more efficiently, while 61% acknowledged the potential threat to academic honesty. Additionally, 85% reported that AI improved their digital literacy and preparedness for a technology-driven work environment. Ethical challenges, such as dependency and violations of academic integrity, emerged as major concerns. In conclusion, AI holds significant potential to support learning, but its use must be accompanied by ethical awareness and effective communication within the educational environment.